Definition of a new blood cell count score for early survival prediction for non-small cell lung cancer patients treated with atezolizumab: Integrated analysis of four multicenter clinical trials - Zhou, Jian-Guo; Wong, Ada Hang-Heng; Wang, Haitao; Jin, Su-Han; Tan, Fangya; Chen, Yu-Zhong; He, Si-Si; Shen, Gang; Frey, Benjamin; Fietkau, Rainer; Hecht, Markus; Carr, Shamus R.; et al. (Frontiers in Immunology, 2022)
Importance Blood cell count test (BCT) is a robust method that provides direct quantification of various types of immune cells to reveal the immune landscape to predict atezolizumab treatment outcomes for clinicians to decide the next phase of treatment. Objective This study aims to define a new BCTscore model to predict atezolizumab treatment benefits in non-small lung cell cancer (NSCLC) patients. Design, Setting, and Participants This study analyzed four international, multi-center clinical trials (OAK, BIRCH, POPLAR and FIR trials) to conduct post-hoc analyses of NSCLC patients undergoing atezolizumab (anti-PD-L1) single-agent treatment (n = 1,479) or docetaxel single-agent treatment (n = 707). BCT was conducted at three timepoints: pre-treatment (T1), the first day of treatment cycle 3 (T2), and first day of treatment cycle 5 (T3). Univariate and multivariate Cox regression analyses were conducted to identify early BCT biomarkers to predict atezolizumab treatment outcomes in NSCLC patients. Main Outcomes and Measures Overall survival (OS) was used as the primary endpoint, whereas progression-free survival (PFS) according to Response Evaluation Criteria in Solid Tumors (RECIST), clinical benefit (CB), and objective response rate (ORR) were used as secondary endpoints. Results The BCT biomarkers of neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) at timepoint T3 and neutrophil-to-monocyte ratio (NMR) at timepoint T2 with absolute cutoff values of NLR_T3 = 5, PLR_T3 = 180 and NMR_T2 = 6 were identified as strong predictive biomarkers for atezolizumab (Ate)-treated NSCLC patients in comparison to docetaxel (Dtx)-treated patients regarding OS (BCTscore low-risk: HR Ate vs Dtx = 1.54 (95% CI: 1.04-2.27), P = 0.031; high-risk: HR Ate vs Dtx = 0.84 (95% CI: 0.62-1.12), P = 0.235). The identified BCTscore model showed better OS AUC in the OAK (AUC12month=0.696), BIRCH (AUC12month=0.672) and POPLAR+FIR studies (AUC12month=0.727) than that of each of the three single BCT biomarkers. Conclusion and Relevance The BCTscore model is a valid predictive and prognostic biomarker for early survival prediction in atezolizumab-treated NSCLC patients.